Introduction: Border Futures - Cross-border cooperation in the territory of the Hesse/Rhineland-Palatinate/Saarland Regional Working Group - Karina Pallagst; Andrea Hartz; Beate Caesar (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
The aim of the Border Futures Subsection was to shed light on the development of cross-border cooperation in the territory of the Hesse/Rhineland-Palatinate/ Saarland Regional Working Group and to indicate future development paths. This paper introduces the focal points of the research and the approach taken, clarifies the terminology and provides an overview of the papers in this volume.
urn:nbn:de:0156-40970184; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Cross-border cooperation; spatial planning; spatial development; border area; border region